Service Quality, Perceived Price Fairness, and Customer Loyalty in Local Retail: The Mediating Role of Customer Satisfaction and an Islamic Business Ethics Interpretation - Muhammad Umar A; Abd. Azis; Rudin M (Jurnal Ilmu Ekonomi dan Bisnis Islam, 2026)
Customer loyalty in local retail is commonly explained by service quality and pricing; however, the indirect statistical pathway through which these factors are associated with loyalty remains underexamined, particularly from an Islamic business ethics perspective. This study examined the relationships among service quality, perceived price fairness, customer satisfaction, and customer loyalty at Star Kitchen, a local retailer in Palu, Indonesia. Using a cross-sectional design, data were collected from 102 repeat customers through a questionnaire and analyzed using PLS-SEM. Service quality was modeled as a reflective–reflective higher-order construct comprising tangibles, reliability, responsiveness, assurance, and empathy. Service quality and perceived price fairness were positively associated with customer satisfaction, with perceived price fairness exhibiting the stronger association. Among the significant direct paths, customer satisfaction showed the largest association with loyalty, whereas neither service quality nor perceived price fairness was directly associated with loyalty. Mediation analysis indicated indirect-only mediation through customer satisfaction in both relationships. PLSpredict indicated high out-of-sample predictive performance. Islamic business ethics was not measured directly but was applied as a normative interpretive framework. Accordingly, the findings may be interpreted as consistent with amānah, ṣidq, iḥsān, ʿadl, transparency, and mutual consent, without constituting empirical validation of these principles. The study provides contextual evidence from an ordinary local retail setting and identifies customer satisfaction as the principal indirect statistical pathway linking service and price evaluations to loyalty.